Willa of the wood - Beatty, Robert, 1963- (Los Angeles : Disney-Hyperion, 2018)
In the late 1800s, a twelve-year-old nightspirit living in the Great Smoky Mountains despairs as homesteaders destroy her forest habitat, until a chance encounter with a "day-folk" man changes everything she thought she knew about her people--and their greatest enemy.
Age 8-12.
Keywords: Spirits -- Juvenile fiction; Cherokee Indians -- Juvenile fiction; Spirits -- Fiction; Cherokee Indians -- Fiction; Supernatural -- Fiction; Mystery and detective stories; JUVENILE FICTION / Action & Adventure / General; JUVENILE FICTION / Fantasy & Magic; JUVENILE FICTION / Mysteries & Detective Stories; Paranormal fiction; Spirits; Great Smoky Mountains (N.C. and Tenn.) -- History -- 19th century -- Juvenile fiction; Great Smoky Mountains (N.C. and Tenn.) -- History -- 19th century -- Fiction; Mystery fiction; Fantasy fiction; Paranormal fiction; Historical fiction; Detective and mystery fiction; Fiction; Juvenile works